On estimations of the Taylor coefficients of functions from the class Kn(E) - Kirjackis, Eduardas (Lietuvos matematikos rinkinys, 2007)
In the article the estimations of the Taylor coefficients of functions from class Kn(E), formed by holomorphic in unit circle E = |z| <1 functions F(z), F(0) = F(1)(0)= . . .= F(n−1)(0)= 0, F(n)(0) =n!, which have nonvanishing n-th are given.